Role of follicle-stimulating hormone receptor polymorphism in predicting ovarian response to letrozole in women with polycystic ovary syndrome during ovulation induction - Zhu, Xiuxian; Wang, Qiaoling; Lang, Jingwen; Zhi, Yunqing; Fu, Yonglun; Bao, Shihua (Frontiers in Endocrinology, 2025)
BackgroundLetrozole is a first-line treatment for anovulatory infertility in women with polycystic ovary syndrome (PCOS). Despite its widespread use, a significant proportion of patients exhibit non-responsive cycles, limiting treatment efficacy. Identifying predictive markers for ovarian response could enhance the efficiency and cost-effectiveness of ovulation induction. Previous studies have suggested an association between follicle-stimulating hormone receptor (FSHR) polymorphisms and ovarian response, though the precise relationship between these polymorphisms and ovarian response to letrozole remains poorly defined.MethodsThis retrospective study analyzed data from 133 women with PCOS (93 responsive to letrozole and 40 resistant) between January 2021 and May 2024. Demographic data were collected, and genotyping of FSHR single nucleotide polymorphisms (c.2039A>G, rs6166 at position 680, and c.919A>G, rs6165 at position 307) was performed using predesigned TaqMan SNP assays. A binary logistic regression model was employed to evaluate the predictive value of FSHR polymorphisms in letrozole resistance.ResultsThe Asn/Asn polymorphism at position 680 was significantly more prevalent in the letrozole-resistant group (57.5%) compared to the letrozole-responsive group (34.41%) [OR: 1.543 (95% CI, 1.046-2.278), P = 0.013]. Similarly, the Thr/Thr polymorphism at position 307 was more common in the resistance group (57.5% vs. 30.11%) [OR: 1.645 (95% CI, 1.120-2.415), P = 0.003]. Participants with either the Asn/Asn or Thr/Thr polymorphism were more likely to exhibit resistance to letrozole. Logistic regression analysis indicated that the Asn/Asn polymorphism was a potential risk factor for letrozole resistance [OR: 5.227 (95% CI, 0.994-27.490), P = 0.051], while the Thr/Thr polymorphism significantly influenced letrozole response [OR: 7.04 (95% CI, 1.394-35.559), P = 0.018].ConclusionsThe Asn/Asn polymorphism at position 680 and the Thr/Thr polymorphism at position 307 of the FSHR gene may serve as potential predictors of ovulatory failure during letrozole therapy in PCOS patients.